HÁBITOS ALIMENTARIOS Y CONDICIONES PSICOLÓGICAS ASOCIADOS AL SÍNDROME DE INTESTINO IRRITABLE EN UN HOSPITAL PÚBLICO - Medrano Egoávil, Elizabeth (2017)
Introduction: The objective of the present study was to identify food habits and psychological conditions which act as associated factors to Irritable Bowel Syndrome in the outpatient service of gastroenterology at the Huánuco base hospital ESSALUD-2009. Methods: We performed an observational, analytical, longitudinal and retrospective case-control study, matched by age and gender. Cases were people diagnosed of IBS according to the Rome III criteria in 2009. We worked with a sample size of 210 outpatients:105 cases and 105 controls (type1error = 0,05, potency = 0.8, exposed cases probability = 43,5%, exposed controls probability = 25%).Convenience Sampling. Variables studied as risk factors for IBS were food habits and anxiety/depression, measured by a dietary questionnaire adapted and evaluated by expert opinion and HADS score respectively. Results: The average age of patients was 51,32±12,69 years with a gender distribution of 132 females/78males. In the statistical bivariate analysis between risk factors and IBS, statistical significance was found with food habits {(p=0.0000; OR=4.36 (IC 95% 2,03 – 9,83)}. We analyzed clinical characteristic of patients and relationship was found between IBS and the following variables: skips dinner (74,3%), eat slowly (73,5%), eat out of home (63,1%), take drugs (67,3%), time before going to the bed≤ 1hour (68,8%) and abdominal discomfort or pain with food (76,1%), all of them with an IC = 95% and p <0.05. Conclusions: Changes in food habits have shown to be present in persons having Irritable Bowel Syndrome. The IBS is related to the omission of dinner, slow intake rate, meals away from home, drug use, time before going to the bed ≤ 1hour and the presence of abdominal discomfort or pain with the ingestion of certain foods.